Aneurysms of the Intracranial Segment of the Ophthalmic Artery Trunk: Case Report and Systematic Literature Review - Peschillo, Simone; Biraschi, Francesco; Diana, Francesco; Colonnese, Claudio; Marenco, Marco; Delfini, Roberto (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2018)
Aneurysms arising from the ophthalmic artery trunk (OAT) are very rare, particularly in the artery's intracranial course. The onset of a subarachnoid hemorrhage (SAH) from a ruptured OAT aneurysm in this segment is extremely rare. We present a case and discuss the anatomy, clinical significance, and therapeutic options for an aneurysm at this site. We also retrospectively analyzed the record of a patient with a ruptured aneurysm of the intracranial segment of the OAT and conducted a comprehensive and systematic review of the PubMed and Scopus databases for literature on this pathology. Only one case report of SAH from an aneurysm of the intracranial segment of the OAT was published in the literature. Only in our case was the intracranial OAT segment aneurysm discovered in the acute phase of SAH. Conventional angiography with three-dimensional acquisition may help detect aneurysms at this level. Detailed knowledge of the anatomy of the OAT is of paramount importance for both surgical and endovascular approaches. Surgical treatment is complex because of difficulties in accessing the orbital region and the risk of optic nerve and vascular injuries. Endovascular treatment, when feasible, could be a good alternative to reduce the risk of loss of vision related to surgical manipulation.
Keywords: systematic review; aneurysm; subarachnoid hemorrhage; ophthalmic artery